Synthesis and characterisation of brannerite compositions (U0.9Ce0.1)1−xMxTi2O6 (M = Gd3+, Ca2+) for the immobilisation of MOX residues. Issue 4 (9th January 2018) - Bailey, D. J.; Stennett, M. C.; Ravel, B.; Grolimund, D.; Hyatt, N. C.
Abstract : This work presents the synthesis and characterisation of novel brannerite ceramics designed for the disposal of mixed oxide fuel residues. Abstract : A suite of uranium brannerites for the disposal of MOX residues, formulated (U0.9 Ce0.1 )1− x M x Ti2 O6 (M = Ca 2+ and/or Gd 3+ ), were prepared using a mixed oxide route under oxidising, inert and reducing atmospheres (air, argon and H2 /N2 ). Gd 3+ was added to act as a neutron absorber in the final Pu bearing wasteform and Ce added to function as a structural analogue for Pu. X-ray powder diffraction of the synthesised specimens found that phase distribution was strongly affected by the processing atmosphere and Gd content. In all cases prototypical brannerite was formed, accompanied by different secondary phases dependent on processing atmosphere. Microstructural analysis (SEM) of the sintered samples confirmed the results of the X-ray powder diffraction. Bulk XANES found that Ti remained in the Ti 4+ oxidation state whereas Ce was uniformly reduced to the Ce 3+ oxidation state regardless of processing conditions or stoichiometry. Micro-focus XANES was used to determine U oxidation in the brannerite phase and showed that U oxidised to higher U oxidation states to charge compensate. It was concluded that the charge balance mechanism was a combination of U oxidation and A-site vacancies.